2018
DOI: 10.3390/agronomy8040038
|View full text |Cite
|
Sign up to set email alerts
|

Field Screening of Waterlogging Tolerance in Spring Wheat and Spring Barley

Abstract: Improved waterlogging tolerance of wheat and barley varieties may alleviate yield constraints caused by heavy or long-lasting precipitation. The waterlogging tolerance of 181 wheat and 210 barley genotypes was investigated in field trials between 2013 and 2014. A subset of wheat genotypes were selected for yield trials in 2015 and 2016. Our aim was to: (1) characterize the waterlogging tolerance of genotypes with importance for Norwegian wheat and barley breeding, and (2) identify which phenotypic traits that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…In such a case, shoot growth can be sustained by the mobilization of nitrogen from older leaves to both younger leaves and the reproductive apex (Colmer and Greenway, 2011). According to Belford et al (1985), the resulting lower N concentration of older leaves is primarily responsible for restricted tiller production in waterlogged wheat, and thus leaf chlorosis and reduced tillering are closely related (de San Celedonio et al, 2016; Sundgren et al, 2018). In the present research, however, reduced N concentration was associated with reduced tillering but not with leaf chlorosis, which became visible in both species only with WL treatments that completely stopped shoot growth (T21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In such a case, shoot growth can be sustained by the mobilization of nitrogen from older leaves to both younger leaves and the reproductive apex (Colmer and Greenway, 2011). According to Belford et al (1985), the resulting lower N concentration of older leaves is primarily responsible for restricted tiller production in waterlogged wheat, and thus leaf chlorosis and reduced tillering are closely related (de San Celedonio et al, 2016; Sundgren et al, 2018). In the present research, however, reduced N concentration was associated with reduced tillering but not with leaf chlorosis, which became visible in both species only with WL treatments that completely stopped shoot growth (T21).…”
Section: Discussionmentioning
confidence: 99%
“…When wheat and barley plants were exposed to waterlogging at tillering, the most affected yield components were spike number, because of either reduced tillering (barley) or tiller fertility (wheat), and the number of kernels per spike (Amri et al, 2014; de San Celedonio et al, 2018; Sundgren et al, 2018). Due to the different architecture of wheat and barley spikes, however, the lower spike yield was related to lower spikelet fertility in the former, and to lower spikelet number in the latter (Masoni et al, 2016; Arduini et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one analysis, Savannah was more tolerant than Bayles partially due to higher root porosity [130]. A recent evaluation of Norwegian genotypes identified tolerant ones that showed specific root traits (e.g., stele and aerenchyma area) in comparison to sensitive cultivars [131,132]. Another experiment demonstrated that the tolerant cultivar Jackson was more tolerant than Coker 9835 probably because of a lower respiration rate [133].…”
Section: Variation In Wheat Waterlogging Tolerancementioning
confidence: 99%
“…According to Haque, Oyanagi & Kawaguchi (2012), De San Celedonio, Abeledo & Miralles (2014), Arduini et al (2016) and Sundgren et al (2018), under waterlogging conditions, seminal roots of wheat are restricted or even die because of decreases in the oxygen concentration in the soil, which would limit water and nutrient uptake by roots, affect the balance between root and shoot growth and accelerate the shoot senescence or even lead to plant death. Setter & Waters (2003) concluded that much research has supported the benefits of adaptive traits for waterlogging including increases in aerenchyma and root porosity.…”
Section: Waterlogging Promoted Senescence Of Leaf and Rootmentioning
confidence: 99%